Instrumen Evaluasi Bentuk Tes - Meli Indah Novita Sari; Wantika W; Agung Agus Refaldi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study uses a descriptive qualitative approach with a literature review method to deeply analyze the forms of evaluation instruments in learning, particularly in the form of tests. The purpose of this study is to understand the various types of tests used in the evaluation process and their advantages and disadvantages. The results of the study indicate that evaluation instruments in the form of tests, both objective and subjective, play a crucial role in assessing student competency achievement in the cognitive, affective, and psychomotor domains. Objective tests such as multiple-choice, true-false, and matching tend to be easy to score and measure factual knowledge. Meanwhile, subjective tests such as essays are more suitable for measuring higher-order thinking skills. A good test instrument must meet the criteria of validity, reliability, objectivity, and practicality so that the evaluation results can be optimally used in the learning decision-making process.